Pendampingan Evaluasi Kebugaran Jasmani dan Pengembangan Motor Skill untuk Meningkatkan Kesiapan Fisik Siswa - Andi Ihsan; Fatoni, Fatoni; Andi Muhammad Rizky Almufarid; Nurhajarurahmah, St. Zulaiha; Raswadi, Mohammad Dika (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
Students' physical readiness is a crucial factor in supporting active participation in educational activities and academic activities in general. State Senior High School 12, located on Satangnga Island, Mattiro Baji Village, Tanakeke Islands District, Takalar Regency, faces limited sports facilities and does not yet have a structured physical fitness evaluation system. This community service activity aims to provide assistance in fitness evaluation and motor skill development to improve students' physical readiness. The method used is participatory training and mentoring through initial assessment stages, material delivery, structured practice exercises based on training circuits and motor games, and a final evaluation. The activity participated in the activity amounted to 40 students. The results of the pre-test and post-test analysis showed significant improvements in the components of cardiorespiratory endurance, muscle strength and endurance, agility, and balance (p < 0.05). This program not only improves students' physical condition but also strengthens teachers' capacity to carry out fitness evaluations independently. This activity is recommended as an adaptive and sustainable physical fitness training model for schools in the island region.